Weaving a Better Future: The Importance of Creating a Path with Emotional Intelligence - Duquette, Patrick; Simon, Joseph (Apprendre et enseigner aujourd’hui, 2024)
Within our educational system, we have often heard equity referred to as the appropriate distribution of resources such as assistive technology, or extra time on exams, with academic success as the goal. We appreciate this view of equity, but we would like to expand it. What if, instead of seeing equity only as the provision of material resources to students, we also saw it as the provision of social and emotional resources ? Furthermore, what if instead of only having academic success as the end goal of education, we also aimed for students’ well-being ? Moreover, we would also like to argue that by doing this we would also be able to enhance their chances of success in life beyond academics. Allow us to explain.